Effect of high-copper diet on transference of blaCTX−M genes among Escherichia coli strains in rats' intestine - Liu, Kang; Li, Linqian; Weng, Mengwei; Zhang, Feng; Guo, Rong; Huang, Jinhu; Yao, Wen (Frontiers in Veterinary Science, 2023)
Both ceftiofur (CTO) and high copper are widely utilized in animal production in China, and the occurrence of CTX-M-carrying Escherichia coli in food-producing animals is increasing. There are some specific associations between in-feed high-level copper and antibiotic resistance, but research in Gram-negative bacteria such as E. coli remains scarce. This study aimed to evaluate the effect of high-copper diet on the horizontal transfer of blaCTX−M−1 among E. coli. A total of 32 male SPF rats aged 21 days were randomly assigned to the following four groups: control (6 mg/kg in-feed copper, C−), high copper (240 mg/kg in-feed copper, H−), CTO (6 mg/kg in-feed copper with oral CTO administration, C+), and high copper plus CTO (240 mg/kg in-feed copper with oral CTO administration, H+). All rats were orally inoculated with an E. coli strain harboring a conjugative plasmid carrying blaCTX−M−1, and the C+ and H+ groups were given 10 mg/kg of body weight (BW) CTO hydrochloride at 26, 27, and 28 days, while the C− and H− groups were given salad oil at the same dose. Fecal samples collected at different time points were used for the enumeration of E. coli on Mac plates or for molecular analysis using PCR, pulsed-field gel electrophoresis (PFGE), S1-PFGE, and Southern-blot hybridization. The results showed that the number of the blaCTX−M−1 gene in the H− group was higher and that the loss speed of this gene was slower compared with the C− group. After administration of CTO, the counts of cefotaxime-resistant E. coli were significantly higher in the C+ group than that in the corresponding control group (C+ vs. C−; H+ vs. H−). In the in vitro test, the results showed that the transfer rates of the conjugation induced by the H− (12 mmol/L) group were significantly higher than that of low copper (2 mmol/L) group. The indigenous sensitive isolates, which were homologous to the blaCTX−M-positive isolates of rat feces, were found by PFGE. The further analysis of S1-PFGE and Southern-blot hybridization confirmed that the blaCTX−M−1 gene in new transconjugants was derived from the inoculated strain. Taken together, high-copper diet facilitates the horizontal transfer and maintenance of the resistant genes in the intestine of rats, although the effects of antibiotics on bacterial resistance appearance and maintenance are more obvious.